Market capacity from the viewpoint of logistic analysis - Knyvienė, Indrė; Girdzijauskas, Stasys; Grundey, Dainora (Technological and Economic Development of Economy, 2010)
The paper discusses market potential and market capacity as a relevant problem of logistic analysis in economy. The emphasis is laid on the concept of market capacity which is comprehended as market potential (the other term occasionally referred to is, potential capital') and which is also the highest possible, from a theoretical viewpoint, amount of product/service sales that could be reached within a certain period of time by all the companies in the market. The paper focuses on the actually complete market (actually covered market) and on market niche (the uncovered part of markets). Studies show that from the viewpoint of logistic analysis, markets can be divided according to their closure. It has been established that according to the degree of closure a market can be open, close and intermediate. Possible scenarios of partly closed market formation have been studied. Results show that with the intensification of market closure, the economic system is essentially changing its behaviour.Article in English.Rinkos talpa: logistinės analizės požiūrisSantrauka. Straipsnyje aptariamos rinkos potencialo ir rinkos talpos dimensijos kaip nūdienos ekonomikos problemų sprendimo galimybė logistines analizės požiūriu. Autoriai nagrinėja užpildytą (prisotintą) rinką (praktiškai aprėpta rinką) ir nišos rinką (neaprėpta rinkos dalį). Vertinant iš logistines analizės perspektyvos, rinkos gali būti skirstomos pagal jų uždarumą. Nustatyta, kad pagal uždarumo laipsnį rinka gali būti trejopa: atvira, uždara ir vidutiniškai uždara. Išnagrinėti galimi iš dalies uždaros rinkos formavimosi scenarijai. Tyrimo rezultatai rodo, kad intensyvėjant rinkos uždarumui ekonomikos sistema keičia savo elgseną.Reikšminiai žodžiai: rinkos talpa, atskirtis, logistinė analizė, paklausa, pasiūla.First published online: 10  Feb 2011